2004
DOI: 10.1016/j.smallrumres.2003.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Field pea (Pisum sativum) inclusion in corn-based lamb finishing diets

Abstract: Two hundred crossbred lambs were used to determine energy value and optimum inclusion level of field pea (Pisum sativum) in corn-based diets. In experiment one (Exp. 1), 100 crossbred lambs (33.9 ± 1.3 kg initial BW) were blocked by weight and sex (two blocks of ewe lambs per treatment; three blocks of ram lambs per treatment) and fed for 89 days. In experiment two (Exp. 2), 100 crossbred ram lambs (39.1 ± 0.2 kg initial BW) were blocked by weight (five pens per treatment) and fed for 63 days. Treatments for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 12 publications
4
19
0
Order By: Relevance
“…The starch coûtent of barley used for the calculation was 65% (NRC, 1996). This value is very similar to that of field pea (47%; Loe et al, 2004). Likewise, CP is similar between both treatments (21.4 and 19.9% for field pea and BCM1360, respectively; Table 2).…”
Section: Exp Illsupporting
confidence: 77%
See 1 more Smart Citation
“…The starch coûtent of barley used for the calculation was 65% (NRC, 1996). This value is very similar to that of field pea (47%; Loe et al, 2004). Likewise, CP is similar between both treatments (21.4 and 19.9% for field pea and BCM1360, respectively; Table 2).…”
Section: Exp Illsupporting
confidence: 77%
“…Less severe effects of field pea on forage iutake were expected than those observed with barley (Boyles et al, 1998;Lardy et al, 2004) or corn (Chase and Hibberd, 1987;Sansón et al, 1990;Pordomiugo et al, 1991) supplementation, because field peas have moderate starch content and relatively high CP (47% starch and 21% CP; Loe et al, 2004). Forage intake was expected to be similar between FP1360 aud BCM1360 because the same amount was fed and they had similar starch and CP content.…”
Section: Exp Illmentioning
confidence: 97%
“…Field pea is one of the most important legume seeds for organic farming (Khalili et al 2002). Field peas have high ruminal protein degradability, high energy value, but have rather low crude protein (CP) content (Loe et al 2004). Alternatively, field bean (FB) is higher in CP (Luke 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the use of legume grains as alternative protein sources for sheep have largely been related to meat production (Vasta et al 2008), and have shown partial or total replacement of soybean with chickpea (Hadjipanayiotou 2002;Christodoulou et al 2005), faba bean (Lanza et al 1999;Antongiovanni et al 2002;Lanza et al 2011), and pea (Lanza et al , 2011Loe et al 2004). These protein sources have no adverse effects on lamb growth rate or on carcass and meat characteristics, and are able to increase the amount of omega-3 fatty acids (FA) in the intramuscular fat Lanza et al 2011;Scerra et al 2011).…”
Section: Introductionmentioning
confidence: 99%